Study of material properties of carbon nanotube composites - Wong, Chin Yeung. (2008)
This study focuses on the material properties of a carbon nanotube - polymer composite with potential applications in alternatives to metallic conductor trace, currently dominated by the use of copper or gold, for plastic circuit board (PCB) signal, ground and transmission line traces as well as 1st and 2nd level interconnects in semiconductor packaging applications.